2023
DOI: 10.3390/cells12040653
|View full text |Cite
|
Sign up to set email alerts
|

Promising Perspectives of the Antiproliferative GPER Inverse Agonist ERα17p in Breast Cancer

Abstract: The estrogen receptor α (ERα) corresponds to a large platform in charge of the recruitment of a panel of molecules, including steroids and related heterocyclic derivatives, oligonucleotides, peptides and proteins. Its 295–311 region is particularly targeted by post-translational modifications, suggesting that it could be crucial for the control of transcription. In addition to anionic phospholipids, the ERα 295–311 fragment interacts with Ca2+-calmodulin, the heat shock protein 70 (Hsp70), ERα and possibly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…We believe that the interesting and timely issues raised by the article of E. Prossnitz and M. Barton would benefit from the addition of recent findings, in particular with respect to the list of GPER modulators including ERα17p and PLMI, as well as others, namely aldosterone, the diphenylacrylamide derivative STX and, possibly, the amyloid β1-42 peptide ( Evans, 2019 ), and related physiological roles resulting from membrane-initiated signaling. A comprehensive review recapitulating the aforementioned data has been recently published ( Kampa et al, 2023 ). Overall, we would like to highlight the relevance of considering this peptide in the list of GPER modulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the interesting and timely issues raised by the article of E. Prossnitz and M. Barton would benefit from the addition of recent findings, in particular with respect to the list of GPER modulators including ERα17p and PLMI, as well as others, namely aldosterone, the diphenylacrylamide derivative STX and, possibly, the amyloid β1-42 peptide ( Evans, 2019 ), and related physiological roles resulting from membrane-initiated signaling. A comprehensive review recapitulating the aforementioned data has been recently published ( Kampa et al, 2023 ). Overall, we would like to highlight the relevance of considering this peptide in the list of GPER modulators.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is worth noting that ERα17p shares structural analogies with PBX1, a pyrrolobenzoxazinone acting as a GPER antagonist ( Maggiolini et al, 2015 ; Lappano et al, 2019 ). Moreover, docking studies showed that ERα17p interacts in the low micromolar range through its N-terminal PLMI motif with the same extracellular GPER pocket, and more specifically through hydrogen and hydrophobic contacts with the residues Gln-138, Pro-192 and Ala-209, as displayed by other ligands ( Lappano et al, 2019 ; Kampa et al, 2023 ). These observations suggested that the PLMI motif could play an important role in driving the action of ERα17p ( Leiber et al, 2015 ; Lappano et al, 2019 ; Jouffre et al, 2023 ).…”
Section: From the Discovery To The Anti-proliferative Anti-nociceptiv...mentioning
confidence: 99%
“…The same biological effect was caused by the N-terminal short synthetic tetrapeptide, formed by Pro295-Leu296-Met297-Ile298 (PLMI) of ERα17p, which is accommodated within the extracellular GPER ligand-binding site and shares some structural similarities with the GPER antagonist PBX1 [47,48]. The N-terminal Pro295 of ERα17p and PLMI forms a hydrogen bond with either the Gln138 or Ala209, hydrophobic interactions with Pro192, and the C-terminal Ile298 points towards Ile279 [68].…”
Section: Non-canonical Gper Ligandsmentioning
confidence: 99%
“…In a mouse xenograft model of breast cancer, GPER activation increases tumor growth and expression of HIF1, VEGF, and the endothelial marker CD34 [ 98 ]. Conversely, in this model, the use of a GPER inhibiting peptide exerts apoptosis and induces a significant decrease in the size of triple-negative mammary tumors in mice [ 99 ]. Activation of the membrane receptor GPER would then appear to have a pro-tumor effect and could play a role in the acquisition of resistance to hormone therapy, with SERMs acting as agonists of this receptor [ 100 , 101 , 102 ].…”
Section: Er-positive Breast Cancermentioning
confidence: 99%